ضغوط الحياة وعلاقتها بالصمود الاكاديمي لدي الطلبة العمال - الأطرش,خولة; حميداتو,نجاح (University of Eloued جامعة الوادي, 2024)
ملخص الدّراسة باللغة العربية: تهدف هذه الدراسة إلى التعرف على طبيعة العلاقة بين ضغوط الحياة والصمود الأكاديمي لدى الطالب الجامعي العامل, كما تهدف أيضا إلى الكشف عن الفروق في مستوى ضغوط الحياة والصمود الأكاديمي بين الجنسين, والتعرف على الفروق في مستوى ضغوط الحياة والصمود الأكاديمي تبعًا للحالة الاجتماعية( متزوج/ غير متزوج). ومن أجل تحقيق هذه الأهداف تم تطبيق الدراسة على عينة متكونة من(100) طالب وطالبة جامعيين من قسم علم النفس وعلوم التربية بجامعة الوادي, تم اختيارهم بالطريقة القصدية, واستخدمنا المنهج الوصفي بأسلوبي الارتباط والفروق، وبعد جمع البيانات ومعالجتها بالأساليب الاحصائية المناسبة وبالاعتماد أيضا على برنامج التحليل الاحصائي SPSS)) تم التوصل إلى النتائج التالية: - تتميز ضغوط الحياة لدى أغلبية الطلبة الجامعيين العمال بمستوى مرتفع. - يتميز الصمود الأكاديمي لدى أغلبية الطلبة الجامعيين العمال بمستوى مرتفع. - توجد علاقة ارتباطية دالة إحصائيا بين ضغوط الحياة والصمود الأكاديمي. - لا توجد فروق دالة إحصائيا بين (الذكور/الاناث) من الطلبة الجامعيين العمال على مقياس ضغوط الحياة. - لا توجد فروق دالة إحصائيا بين (الذكور/الاناث) من الطلبة الجامعيين على مقياس الصمود الأكاديمي. - لا توجد فروق دالة إحصائيا بين الطلبة الجامعيين العمال على مقياس ضغوط الحياة تبعا للحالة الاجتماعية (متزوج/ غير متزوج). - لا توجد فروق دالة إحصائيا بين الطلبة الجامعيين العمال على مقياس الصمود الأكاديمي تبعا للحالة الاجتماعية(متزوج/غير متزوج). Abstract: The study aims to identify the of the relationship between life pressures and academic resilience among working university students . It also aims to reveal differences in the level of life stresses and academic resilience according to marital status …in order to achieve these goals the study I was applied to a sample of 100 male and female university students from the Department of psychology and Educational sciences at the University of the yearly . They were selected using a purposive method and we used the descriptive approach using the differences method after collecting the data and processing it with appropriate statistic methods and also relying on the program Statistical analysis led to the following results - The life pressures of the majority of working university students are characterized by a high level . - The academic resilience of the majority of working university students is characterised by a high level - There is a statistically significant correlation between life pressures and academic resilience - There are no statistically significant differences between male /female students University workers on the life stress scale - There are no statistically significant differences between male / female students university students on the academic resilience scale - There are no statistically significant differences between working university students on the scale life pressures depending on marital status married , unmarried
Keywords: الصمود الأكاديمي; ضغوط الحياة; academic resilience; life pressures